Geography in America at the Dawn of the 21st Century 2004
DOI: 10.1093/oso/9780198233923.003.0026
|View full text |Cite
|
Sign up to set email alerts
|

Transportation Geography

Abstract: Transportation geography is the study of the spatial aspects of transportation. It includes the location, structure, environment, and development of networks as well as the analysis and explanation of the interaction or movement of goods and people (Black 1989). In addition it encompasses the role and impacts—both spatial and aspatial—of transport in a broad sense including facilities, institutions, policies and operations in domestic and international contexts. It also provides an explicitly spatial perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The analysis strengthens the applicability of the rather 'ghettoized' dimension of transport geography (cf. Goetz et al, 2003;Keeling, 2007) in general to port geography papers given the somewhat limited impact of its core papers externally and its growing specialization within transport research moving away from mainstream geographical research, except for the top cited papers that have actually limited connections with classical port geography papers. Yet this study has identified a recent production of more innovative papers connecting both classical port geography papers and wider research fields, backed by the emergence of a connected community of port specialists.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis strengthens the applicability of the rather 'ghettoized' dimension of transport geography (cf. Goetz et al, 2003;Keeling, 2007) in general to port geography papers given the somewhat limited impact of its core papers externally and its growing specialization within transport research moving away from mainstream geographical research, except for the top cited papers that have actually limited connections with classical port geography papers. Yet this study has identified a recent production of more innovative papers connecting both classical port geography papers and wider research fields, backed by the emergence of a connected community of port specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally there is some debate about what these actually are. In essence, transport geography is the study of spatial aspects of transport (Goetz et al, 2004). Rodrigue et al (2009) identify as important the geography of transport networks themselves and the impact of these networks in determining wider human geographies, and to this might be added the concept of travel spaces (Shaw et al, 2008).…”
Section: Links and Prospects: Where Transport Matters 1 Transport And Transport Geographymentioning
confidence: 99%
“…More recently, the inheritors of the behavioral and historical^cultural tradition (as well as its long-time practitioners) have discussed network behavior in terms of actors and strategy. This more recent writing has begun to reengage with theoretical debates across broader literatures in geography, although internal critics still feel compelled to call for greater openness towards different epistemological stances (Goetz et al, 2004;Hanson, 2000).…”
Section: Network In Transportation Geographymentioning
confidence: 99%